Eosinophils, probiotics, and the microbiome - Rosenberg, Helene F.; Masterson, Joanne C.; Furuta, Glenn T. (Journal of leukocyte biology, 2016)
Review on the relationship between eosinophils, endogenous microbial flora, and probiotic bacteria, to encourage research in this field. There is currently substantial interest in the therapeutic properties of probiotic microorganisms as recent research suggests that oral administration of specific bacterial strains may reduce inflammation and alter the nature of endogenous microflora in the gastrointestinal tract. Eosinophils are multifunctional tissue leukocytes, prominent among the resident cells of the gastrointestinal mucosa that promote local immunity. Recent studies with genetically altered mice indicate that eosinophils not only participate in maintaining gut homeostasis, but that the absence of eosinophils may have significant impact on the nature of the endogenous gut microflora and responses to gut pathogens, notably Clostridium difficile. Furthermore, in human subjects, there is an intriguing relationship between eosinophils, allergic inflammation, and the nature of the lung microflora, notably a distinct association between eosinophil infiltration and detection of bacteria of the phylum Actinobacteria. Among topics for future research, it will be important to determine whether homeostatic mechanisms involve direct interactions between eosinophils and bacteria or whether they involve primarily eosinophil‐mediated responses to cytokine signaling in the local microenvironment. Likewise, although is it clear that eosinophils can and do interact with bacteria in vivo, their ability to discern between pathogenic and probiotic species in various settings remains to be explored.